Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (CLARISSA Research and Evidence Paper, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.

“Everyone is talking about it, but no one is doing it”: How implementation research is – or isn’t – informing adaptation towards scale in international education - Dowd, Amy Jo (International Journal of Educational Development, 2024)
With growing evidence of what works in education, governments and their partners strive towards scale. While implementation research to adapt solutions holds promise for testing what works, where and for whom, its use in education is limited. Sixty-three international education stakeholders from government, academia, think tanks, local and international non-governmental organizations, multi- and bi-laterals and foundations offer insight into three modes of implementation research that differ on responsiveness, timeliness and stakeholder collaboration. They speak to the primacy of government involvement, trust and curiosity in collaborative efforts. This study explores enabling factors for evidence-based implementation improvement on the pathway to scale.
Keywords: Evidence-based practice; Implementation research; International education

Social Accountability 3.0: Engaging Citizens to Increase Systemic Responsiveness. Background Paper - Guerzovich, Florencia; Aston, Tom (Grupo Politeia, ESAG, UDESC and act4delivery, 2024)
Social accountability has become increasingly important to development programming since the 2004 World Development Report spearheaded its first generation of programming. In 2016, Thomas Carothers synthesized global experts’ perspectives on what became known as the second generation. With an evolving global context, new research and evaluations and tacit knowledge on how those assumptions played out in practice, the time is ripe for asking what the evidence since 2004 can tell us about what the social accountability’s next generation might look like? This meta-analysis takes stock of that knowledge through a systems lens and presents a possible “social accountability 3.0.” It draws on a database of 157 cases of initiatives implemented by different civil society organizations around the world and the lived experience of practitioners. Scholarly debates present practitioners’ options in binary terms, contrasting 1.0 minimalist and 2.0 maximalist options. The review finds that this binary is inaccurate and misleading; it masks practitioners’ diverse interpretations of 2.0 and range of feasibility considerations. Instead, work in the last decade looks more like a mosaic. By opening the analysis to the broader range of evidence, and reflecting more critically on scholars’ assumptions, a more adaptable middle path for social accountability 3.0 emerges. Its key outcomes include contributing to systemic responsiveness and an operational mechanism to rework the social contract.

A Framework for Embedding Learning in Systems Change - Bertermann, Kecia; Coffman, Julia (Center for Evaluation Innovation, 2024)
This five-step framework, developed and tested by a foundation, embeds learning in emergent systems change strategies. It prioritizes the testing of hypotheses and assumptions, uses learning questions, and calls for examining both confirming and disconfirming evidence. --- A framework for embedding learning in systems change strategies and for testing strategic uncertainties. Learning and evaluation approaches that accompany systems change efforts need to fit with and support the emergent nature of this work. Systems change efforts call for examining, with evidence, the hypotheses and assumptions that undergird the work and regularly adapting in response to what is learned. They require staff to be highly engaged in testing their ideas by gathering evidence, interpreting it, and then acting on its implications. This brief presents a learning approach—referred to here as the Learning Framework—developed and tested by a foundation to support its systems change strategies. It is intended for other practitioners working on approaches for integrating learning with systems change efforts. Because a wealth of conceptual work exists about why learning is critical to systems change but practical advice about how to do it is much less available, we describe the approach we took and how the Framework’s core elements fit together in practice. The primary purpose of this approach is to interrogate our strategic uncertainties. This approach to learning is different from the dominant approach to learning and evaluation in philanthropy that primarily looks for evidence (often static metrics) that expected outcomes have been achieved (an approach that is more suitable for linear and predictable change strategies). This Learning Framework is driven by, and organized around, hypotheses and assumptions. This is especially important for systems change efforts where the path forward cannot be determined with complete certainty, but where robust evidence collection and regular sensemaking can increase our confidence in chosen directions and ultimately increase our chances of success.

Disentangling Government Responses: How Do We Know When Accountability Work is Gaining Traction? - Fox, Jonathan; Halloran, Brendan; Fölscher, Alta; McGee, Rosie (Working Paper, 2024)
Advocacy for public accountability aims to produce certain reactions from government officials or service providers. However, the reactions can be many and diverse, and it is not always clear to advocates how to interpret them and decide on next steps—whether to intensify efforts or back off; continue the same strategy or make adjustments. This paper presents a framework to help accountability advocates and practitioners interpret government reactions to their efforts and move forward appropriately. The framework arises from learning and reflection in the context of the International Budget Partnership (IBP)’s Strengthening Public Accountability with Results and Knowledge (SPARK) program. SPARK seeks to bolster the collective agency of marginalized communities and coalitions to advance democratic and equitable fiscal governance systems that channel public resources to services that address the priority needs of these historically excluded groups. The paper: · unpacks the broad umbrella category of government responses to citizen-led accountability initiatives, discerning within it three overlapping categories of responses, responsiveness, and accountable responsiveness (RRA), and pinpointing what distinguishes them; · maps out the public financial management (PFM) system as the critical conduit for any public service to progress from non-response through these three categories, reflecting the terrain and priorities of the SPARK program and IBP more broadly. Looking at RRA in the context of this PFM map offers key insights for the twin tasks of tracing and unblocking bottlenecks in resource management systems that hinder responsiveness and accountability, as well as demanding specific reforms that make the fiscal governance system more open to citizen engagement; and · discusses how the RRA framework can be used to take stock of partial or incremental responses and assess whether change is moving towards accountable governance, by reference to the SPARK program and other IBP efforts. The RRA framework supports accountability-claiming practice by facilitating close attention to the actions of and influences on key government stakeholders, careful interpretation of these, and consequential adjustments to advocacy strategies. Its implications for monitoring, evaluating, and learning (MEL) from practice are also significant. MEL has been evolving in the accountability field in line with the thinking and practical challenges behind the development of the RRA framework. The framework adds to a range of emerging approaches that support the application theories of change, evidence-based adaptive programming, and politically aware systems thinking in the complex task of building accountable responsiveness towards constituencies historically excluded from public goods and services, and ultimately equitable development outcomes from an intersectional perspective.
Keywords: Development studies; Public policy; Social policy